Identification of protein biomarkers of mercury toxicity in fish - Vieira, José Cavalcante Souza [UNESP]; Braga, Camila Pereira; de Oliveira, Grasieli [UNESP]; de Lima Leite, Aline; de Queiroz, João Vitor [UNESP]; Cavecci, Bruna [UNESP]; Bittarello, Alis Correia [UNESP]; Buzalaf, Marília Afonso Rabelo; Zara, Luiz Fabricio; de Magalhães Padilha, Pedro [UNESP] (Springer Nature, 2017)
Bioaccumulative metals such as mercury are found in increasing amounts in fish and their consumers. In the region of the Madeira River, in the Brazilian Amazon, mercury (Hg) is a predominant contaminant in the aquatic ecosystem. There is therefore a need to find specific biomarkers of mercury toxicity in fish to monitor contaminations. Here, mercury-bound proteins were identified in the liver tissues of fishes Mylossoma duriventre and Brachyplatystoma rousseauxii. Mercury was quantified in liver tissue, pellets and protein spots by graphite furnace atomic absorption. Proteins were fractionated by two-dimensional polyacrylamide gel electrophoresis and identified by mass spectrometry with electrospray ionization. We identified nine proteins linked to mercury and that presented biomarker characteristics of mercury. Among the proteins identified, isoforms of parvalbumin, ubiquitin-40S ribosomal protein S27a, brain-specific angiogenesis inhibitor 1-associated protein 2-like protein 2 and betaine–homocysteine S-methyltransferase 1 are notable for having the molecular function of binding to metallic ions.
Keywords: Atomic absorption spectrometry; Biomarkers; Mass spectrometry; Mercury in fish; Metalloproteomics; Proteins